1996
DOI: 10.1007/bf02484403
|View full text |Cite
|
Sign up to set email alerts
|

Ion microscopic imaging of calcium during 1,25-dihydroxyvitamin D-mediated intestinal absorption

Abstract: A combination of ion microscopic and conventional radionuclide techniques was employed to investigate the temporal-spatial dynamics of 1,25-dihydroxyvitamin D3 [1,25(OH)2D3]-stimulated intestinal calcium (Ca) absorption. At varying times following the administration of a single intravenous dose of 1,25(OH)2D3 to vitamin D-deficient chicks, transepithelial transport and tissue retention of Ca were quantitated in vivo, using the ligated duodenal loop technique and 47Ca as the tracer. The localization of Ca in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The asymmetric (higher apical than basal) cytoplasmic distribution of CBP that we find in the cow trophoblast cells has also been reported in chicken enterocytes for 28CBP (Thorens et al 1982;Nemere et al 1991) and correlates with the initial localization of 47 Ca uptake by ion microscopy in this system (Fullmer et al 1996). It could represent a transient store or a device to enhance the rate of facilitated diffusion.…”
Section: Discussionsupporting
confidence: 86%
“…The asymmetric (higher apical than basal) cytoplasmic distribution of CBP that we find in the cow trophoblast cells has also been reported in chicken enterocytes for 28CBP (Thorens et al 1982;Nemere et al 1991) and correlates with the initial localization of 47 Ca uptake by ion microscopy in this system (Fullmer et al 1996). It could represent a transient store or a device to enhance the rate of facilitated diffusion.…”
Section: Discussionsupporting
confidence: 86%
“…By contrast, duodenal CaT1 and, to a lesser degree, ECaC RNA levels were dramatically and consistently down-regulated in the Tokyo and the Leuven KOs. Until recently, the unidentified calcium influx mechanism was not regarded as primordial, as calcium entered into the enterocyte even in the absence of vitamin D (15,24,34). Surprisingly, the present duodenal gene expression pattern indicates that, among the candidate calcium-transporting genes, only CaT1 and ECaC are severely impaired in VDR-KO mice.…”
Section: Discussionmentioning
confidence: 68%
“…This may imply a regulatory role for the epithelial calcium channels in active calcium absorption or a more complex regulation driven by the interaction between calcium influx and calbindin-D 9K . The permanent activation of these channels may indeed require the immediate intracellular uptake of each calcium molecule delivered through the channel by calbindin-D 9K , with subsequent mobilization of calcium toward the basolateral membrane (24,34,35). In this view, the major down-regulation of CaT1 and ECaC expression combined with a reduced calbindin-D 9K expression may contribute to the more profound hypocalcemia and reduced calcium in bone of the Tokyo KO on the normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion studies, however, have revealed that neither protein is essential for vitamin D-mediated calcium uptake as the loss of the genes for calbindin D9K or calbindin D28K expression did not alter intestinal sensitivity to 1,25(OH) 2 D 3 (14 -16). Rather, these proteins were eventually deemed to be calcium-sensitive buffer components likely involved in the shuttling of calcium to organelles within the cytoplasm (17). Interestingly, although both S100g and Calb1 were identified early on as direct targets of vitamin D action (18,19), the molecular details through which their expression is enhanced by 1,25(OH) 2 D 3 is currently unclear.…”
mentioning
confidence: 99%